Sociopolitical perspectives on language policy and planning in the USA - Huebner, Thom; Davis, Kathryn Anne; Lo Bianco, Joseph (Studies in bilingualism, 1999)
This volume is the result of a colloquium on socio-political dimensions of language policy and language planning held at the 1997 American Association of Applied Linguistics (AAAL) Conference. The focus is on language planning and policy in the USA, but the issues raised will be applicable to other parts of the world as well. Three broad issues are addressed: general aspects, case studies dealing with certain languages or ethnic groups, and language planning in practice. The first, general, part, provides a historical analysis of language planning and language policy in the US, and proceeds to.